Research Support Services: Agriculture - Olsen, Livia M. S.; Farmer, Diana (My University, 2017)
This report is a result of an Ithaka S+R project to investigate research support services at research libraries for agricultural researchers. Nineteen institutional libraries, mostly at land grant universities, collaborated with Ithaka S+R on this project. Librarians at Hale Library interviewed agricultural researchers at K-State. Interview transcripts were sent Ithaka S+R to write a report for the entire project. This report is K-State’s local report which is based on interviews conducted by K-State librarians with K-State agricultural researchers.
Citation: Farmer, D. and Olsen, L. M. (2016). Research support services: Agriculture. Manhattan, KS: K-State Libraries.
Keywords: Agriculture; Research Support; Academic Libraries